2017
DOI: 10.1002/poi3.151
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Popularity, Reputation, and Social Influence in the Twitter Society

Abstract: The pervasive presence of online media in our society has transferred a significant part of political deliberation to online forums and social networking sites. This article examines popularity, reputation, and social influence on Twitter using large-scale digital traces from 2009 and 2016. We process network information on more than 40 million users, calculating new global measures of reputation that build on the D-core decomposition and the bow-tie structure of the Twitter follower network. We integrate our … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 53 publications
1
44
0
Order By: Relevance
“…Our study also identified a novel network characteristic – that is, suicidal youth having higher relative popularity versus nonsuicidal peers – as predicting higher SA rates and more attempts among those considering suicide (SA/Total SI). Popularity is strongly related to social influence (Garcia, Mavrodiev, Casati, & Schweitzer, ), suggesting that popular suicidal youth normalize suicidal behavior. SA rates were also higher when suicidal youth were more clustered (i.e., homophily).…”
Section: Discussionmentioning
confidence: 99%
“…Our study also identified a novel network characteristic – that is, suicidal youth having higher relative popularity versus nonsuicidal peers – as predicting higher SA rates and more attempts among those considering suicide (SA/Total SI). Popularity is strongly related to social influence (Garcia, Mavrodiev, Casati, & Schweitzer, ), suggesting that popular suicidal youth normalize suicidal behavior. SA rates were also higher when suicidal youth were more clustered (i.e., homophily).…”
Section: Discussionmentioning
confidence: 99%
“…Over these texts, we applied a 100-dimensional Doc2Vec [30] model trained on a separate corpus of 1.7 Million biographical texts generated in previous research [31]. Doc2Vec fits a language model that represents documents (in this case bios) as vectors such that semantically and linguistically similar documents are close in the representation space.…”
Section: User Analysismentioning
confidence: 99%
“…An example of such behavior can be a selfie with lifestyle information (Alshawaf and Wen 2015), captioned by using hashtags (Page 2012). Often, they follow limited people and, thus, have a high follower to following ratio, indicating their high influence/popularity (Farwaha and Obhi 2019;Garcia et al 2017). A study also indicated that high numbers of likes can indicate how popular the posts of a person are (Chua and Chang 2016).…”
Section: Popularitymentioning
confidence: 99%